Antibacterial Improvement of Disease-Protective Face Masks Using Gold Nanoparticles (Journal of Pharmaceutical Negative Results, 2022)
In this work, the antibacterial effectiveness of face masks made from polypropylene, against Candida albicans and Pseudomonas aeruginosa pathogenic was improved by soaking in gold nanoparticles suspension prepared by a one-step precipitation method. The fabricated nanoparticles at different concentrations were characterized by UV-visible absorption and showed a broad surface Plasmon band at around 520 nm. The FE-SEM images showed the polypropylene fibres highly attached with the spherical AuNPs of diameters around 25 nm over the surfaces of the soaked fibres. The Fourier Transform Infrared Spectroscopy (FTIR) of pure and treated face masks in AuNPs conform to the characteristics bands for the polypropylene bands. There are some differences in the FTIR patterns for samples containing AuNPs by decreasing band intensities and broadening the peaks by increasing the AuNPs concentration, resulting from the band formation between Au and methylene group in PP. The prepared AuNPs suspension showed decent antibacterial activity against Candida albicans. The antibacterial test showed improvement in the antibacterial of the mask samples soaked in AuNPs suspension against C.albicans and P.aeruginosa pathogenic.